El presupuesto de tarifas de agua de uso agrario y su incidencia en la gestión financiera y económica de la Comisión de Regantes de Jequetepeque - 2016 - Huaman Esteves, Johanna Yessenia (2017)
The objective of this research is to determine the impact of Social Responsibility on the Financial and Economic Situation of the Jequetepeque Irrigation Commission. Considering that the Water Tariff Budget for agricultural use is the main source of income or economic resources (money) that each Organization of Water Users for agricultural use must control to execute and evaluate according to what is established in the current legal framework; which has a direct impact on the financial and economic management of these organizations; whose fulfillment of their objectives will affect the goals and results of each annual period or exercise; so that the research topic will be in favor of the good progress of these organizations. It is unlikely that a company will assume a business management policy under administrative and accounting aspects without the proper elaboration, formulation, execution and evaluation of the Annual Budget for Water User Agencies for agricultural use; such as the Users' Boards and their respective Irrigation Commissions, in our case, the Irrigation Commission of the Jequetepeque district.